Effectiveness of the Combination Warm Compress and Benson Relaxation Therapy in the Labor Process of Mothers - Indah Wulaningsih; Boediarsih Boediarsih; Yohanes Reynaldi Lumowa (GLOBAL HEALTH SCIENCE GROUP, 2026)
Pain and anxiety in mothers during the first stage of labor are two interrelated conditions that can interfere with the effectiveness of contractions and the mother's comfort, where increased pain triggers nerve activation, while anxiety amplifies the perception of pain through the pain–anxiety–tension cycle mechanism. Various non-pharmacological interventions such as warm compresses and Benson relaxation have been proven to help, but the effectiveness of their combination in a pre–post approach has rarely been studied. To determine the effectiveness of combining warm compress therapy and Benson relaxation in reducing pain and anxiety levels in mothers who are about to undergo the labor process in Brotojoyo 3 Room, K.R.M.T Wongsonegoro Hospital, Semarang. Data collection was carried out directly on Mrs. N and Mrs. W, with pain intensity measured using the VAS questionnaire and anxiety levels measured using the HARS questionnaire before (pre-test) and after (post-test) the intervention. The intervention provided consisted of a warm compress for 15 minutes and Benson relaxation for 15–20 minutes. Data analysis was conducted descriptively and comparatively by comparing changes in pain and anxiety scores before and after the intervention for each patient, which were then presented in the form of tables and graphs. The results showed a decrease in pain in the first patient from 6 to 3 and in the second patient from 7 to 4, while anxiety decreased from moderate to low in the first patient and from moderate–severe to moderate in the second patient; vital signs such as pulse and respiration also showed improvement after the intervention. Overall, the combination of warm compresses and Benson's relaxation proved to be effective, safe, and easy to apply in reducing pain and anxiety in first-stage laboring mothers and has the potential to be used as part of the standard non-pharmacological nursing care. Labor pain before intervention in both patients was at a moderate to severe level, whereas after the intervention it decreased by 2–3 levels. Pre-intervention anxiety was at a moderate to severe level, and post-intervention showed a significant decrease, especially in the first patient. The combination of warm compress and Benson relaxation was proven effective in reducing pain intensity, anxiety, muscle tension, and sympathetic responses (pulse, BP, RR). This intervention is suitable to be applied in the delivery room because it is safe, inexpensive, easy to perform, and does not interfere with the physiological labor process. A multimodal approach provides a more positive childbirth experience and enhances the mother's ability to cope with contractions.